Noble Metal versus Abundant Metal Catalysts in Fine Organic Synthesis: Cost Comparison of C–H Activation Methods - Komarova, Alina A.; Perekalin, Dmitry S. (Organometallics, 2023)
There is a common assumption that replacement of the classical catalyst based on rare and expensive noble metals by the catalysts based on earth-abundant metals will dramatically reduce the costs of organic synthesis. Herein we demonstrate that it may not be true, mainly because sophisticated organic substrates and modern reagents are often as expensive as catalytic amounts of noble metals. The particular cost analysis of the syntheses of 3,4-diphenyl-isoquinolone by various C–H activation methods revealed that the main costs fall on the stoichiometric reagents rather than the catalysts. As a result, the metal-free synthesis appears to be even more expensive than the procedures involving ruthenium and rhodium catalysts. Overall, metal prices should not be considered the sole reason for conducting academic research without any preliminary analysis.